The Effect of Nitrogen and Sulfur Fertilization in Combination with Pseudomonas aeruginosa and Seaweed on Agricultural Traits and Seed Yield of Rapeseed (Brassica napus L.) in Fields after Rice (Oryza sativa L.) Harvest - seyyed mohammad Akhgar; Naser Mohammadian roshan; Hamidreza Dorodian; Majid Ashouri; Seyyed mostafa Sadeghi (بوم شناسی کشاورزی)
IntroductionRapeseed (Brassica napus L.) is one of the most important oilseed crops globally, ranking third in oil production after soybean and oil palm. The seeds contain over 40% oil, with rapeseed oil being the only edible oil that includes sulfur-containing fatty acids. Nitrogen is one of the most important nutritional elements and a key factor in achieving optimal yield in rapeseed. The bacterium Pseudomonas aeruginosa is used as a plant growth promoter in agriculture. This bacterium helps increase nitrogen uptake and improve root growth in plants. This study aims to assess the combined effects of nitrogen and sulfur fertilizers and a growth regulator on rapeseed performance in a rice-paddy rotation system.Materials and MethodsA split-factorial experiment was carried out to investigate the effects of nitrogen and sulfur fertilizers, as well as a growth regulator (a blend of Pseudomonas aeruginosa and seaweed), on the yield and quality of rapeseed (Hyola 401 variety) in the second crop following rice cultivation in Gilan Province. The study was designed in a completely randomized block design with three replications over two crop years (2021-2022 and 2022-2023) at a farm located in Bazkiagurab, Lahijan City. The main experimental factors included: (1) the application (or non-application) of a growth regulator at a concentration of 5 mg.L-1, and (2) nitrogen fertilization at four levels (0, 90, 180, and 270 kg.ha-1) using urea (46% N) and sulfur fertilization at three levels (0, 35, and 70 kg.ha-1) using ammonium sulfate (24% S, 12% N).Results and DiscussionThe results revealed that the highest seed yield (4081 kg.ha-1) and oil yield (1135 kg.ha-1) were obtained from the treatment involving the growth regulator, 270 kg.ha-1 of nitrogen, and 70 kg.ha-1 of sulfur. Conversely, the lowest seed yield (1085 kg.ha-1) and oil yield (368 kg.ha-1) were recorded when the growth regulator was applied without nitrogen, and with 70 kg.ha-1 of sulfur fertilizer. The application of nitrogen fertilizer improved soil microbial activity, enhanced the availability of growth hormones and stimulants, and increased nutrient uptake, all of which contributed to higher photosynthesis and improved plant dry matter. These factors played a significant role in boosting seed yieldThe treatment involving 270 kg of nitrogen and 70 kg of sulfur fertilizer resulted in the highest plant height (171.3 cm). In contrast, the lowest plant height (137.3 cm) was observed in the treatment that did not include a growth regulator, nitrogen fertilizer, and only 35 kg.ha-1 of sulfur fertilizer. Additionally, the growth regulator and the nitrogen and sulfur fertilization treatments significantly affected the duration of flowering, vegetative growth, and seed filling (p ≤ 0.01). The longest durations for flowering (31 days), vegetative growth (207 days), and seed filling (82 days) were recorded in the treatment combining 270 kg.ha-1 of nitrogen, 70 kg.ha-1 of sulfur, and the growth regulator.ConclusionThe findings suggest that plant height is strongly influenced by both the number of nodes and the length of internodes, with a significant relationship observed between plant height and the application of nitrogen and sulfur fertilizers. A positive and significant correlation was found between plant height and seed yield, highlighting the importance of plant height in determining seed production. The highest seed yield (4081 kg.ha-1) was achieved when nitrogen and sulfur fertilizers were applied along with the growth regulator. Overall, the interactions between nitrogen and sulfur fertilizers were found to impact grain yield and its components significantly. Future research exploring these interactions, particularly in combination with microbial agents, could provide valuable insights for optimizing rapeseed cultivation and better addressing the nutritional needs of plants.